REVITALISASI PARENTING LUQMAN (USAHA PROGRESIF MEMBANGUN KETAHANAN NASIONAL MELALUI KELUARGA) - Syam, Nur Fadhilah (Al-I'jaz: Jurnal Kewahyuan Islam, 2019)
AbstractBuilding National Resilience is a necessity for the people of Indonesia, building national resilience as well as increasing the nation's immune power to be able to overcome all threats both from the internal of the nation itself and from outside. Building national resilience is the obligation of all Indonesian people, including the role of religion, especially Islam. This paper wants to describe one of the stories from the Qur'an that can be used as students for families and methods of family education in an effort to build national resilience. In this paper the author tries to examine Al-Luqman's parenting in educating his children, then tries to revitalize modern life today. This is based on an analysis of the moral destruction of the younger generation that can destroy the national security of the nation. The research method used in this paper is a central study in which the author collects stori literature, several interpretations and hadith as the main ingredients. So that the conclusion is that character education based on religious guidance in family is a main thing and necessity, to improve the character first. This will have an impact on the character of children in their daily lives